STUDY ON ANTI-HIV ACTIVITY OF DIARYLANILINE DERIVATIVES USING QUANTITATIVE STRUCTURE-ACTIVITY RELATIONSHIP (QSAR) - Ihsanul Arief; Ria Armunanto; Bambang Setiaji (Universitas Gadjah Mada, 2013)
Study on anti-HIV activity of diarylaniline derivative compounds by using quantitative structure-activity relationship (QSAR) has been done. The compounds structure and their anti-HIV activities were obtained from literature. Molecular and electronic parameters were calculated by Austin Model 1 (AM1), Parameterized Model 3 (PM3), Hartree-Fock (HF), and density functional theory (DFT) methods. QSAR analysis was performed using multilinear regression method. The result shows that HF method can produce the best model as follows:log EC50 = 46.418 + (99.360 × qC4) - (67.189 × qC9) - (278.869 × qC15) + (782.466 × qC19) - (127.463 × qO7)n = 20; r2 = 0.815; SEE = 0.393; Fcal/Ftab = 4.185; PRESS = 2.160Those model can predict a good inhibitory activity (log EC50) value of -0.3359 to compound N1-(4′-Cyanophenyl)-5-(4″-cyanovinyl-2″,6″-dimethyl-phenoxy)-4-hydroxyethylbenzene-1,2-diamine).